Decarbonizing Indonesia’s Nickel Smelters: Implications for Energy Security, Carbon Pricing, and Green Finance Policies - Sari, Sholihah Eka Permata; Sasongko, Nugroho Adi; Yoesgiantoro, Donny (PendIPA Journal of Science Education, 2025)
As the world’s largest nickel producer, Indonesia faces critical challenges in decarbonizing its nickel smelting sector while maintaining economic growth. This study addresses the lack of integrated assessments of carbon pricing impacts and green finance mechanisms in Indonesia’s nickel industry, using exclusively secondary data from government reports (BPS, MEMR), global databases (IEA, Global Carbon Atlas), and policy documents. A gate-to-gate Life Cycle Assessment (ISO 14044) reveals that Indonesian nickel smelters emit 14.8 tons CO₂-eq per ton of product (IEA, 2023), 25% higher than the global average. Economic modeling, based on nickel price trends (LME, 2020–2023) and carbon tax scenarios, indicates that a $40/ton CO₂ tax would raise production costs by 15%, reducing export competitiveness by 6.2% under current market conditions. Policy analysis highlights the feasibility of green bonds and fiscal incentives for renewable energy adoption, referencing successful cases in the Philippines (RE Law, 2022). These findings provide a data-driven framework for aligning Indonesia’s nickel industry with its 2060 net-zero target, emphasizing the role of secondary data in shaping low-carbon transitions for resource-rich economies.